2016
DOI: 10.4238/gmr15048890
|View full text |Cite
|
Sign up to set email alerts
|

Blood folic acid, vitamin B12, and homocysteine levels in pregnant women with fetal growth restriction

Abstract: ABSTRACT. Deficiencies in nutrients such as folic acid and vitamin B12 may play a role in fetal growth restriction (FGR). However, whether folic acid, vitamin B12, or homocysteine is associated with FGR in Chinese populations remains unclear. This study investigated the relationship between these nutrient deficiencies and FGR in pregnant Chinese women. We selected 116 mother and infant pairs, and categorized the neonates into the FGR, appropriate for gestational age, and large for gestational age groups. Birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…In two articles, a positive association between RBC folate levels in early pregnancy and neonatal HC was described [32,33]. Similar associations were found with serum folate in one study (R = 0.394, P = 0.044) [39]. This was in contrast to two other studies, which found no association between serum, plasma, and RBC folate concentrations and neonatal HC across all trimesters [38,41].…”
Section: Vitamin Bmentioning
confidence: 71%
See 1 more Smart Citation
“…In two articles, a positive association between RBC folate levels in early pregnancy and neonatal HC was described [32,33]. Similar associations were found with serum folate in one study (R = 0.394, P = 0.044) [39]. This was in contrast to two other studies, which found no association between serum, plasma, and RBC folate concentrations and neonatal HC across all trimesters [38,41].…”
Section: Vitamin Bmentioning
confidence: 71%
“…The study by Takimoto et al (ErasmusAGE score 4) described that neonatal HC was negatively correlated with maternal vitamin B 6 during late pregnancy [31]. Ten studies examined the relationship between serum/plasma folate or red blood cell (RBC) folate concentrations and brain size, including one RCT [32], eight prospective cohort studies [33][34][35][36][37][38][39][40], and one cross-sectional study [41] (Table 1). Serum/plasma folate is indicative of recent folate intake, whereas RBC folate concentrations are useful to measure long-term folate status, as folate accumulates in RBCs during erythropoiesis and remains unvaried across the lifespan of the RBC (approximately 120 days) [42].…”
Section: Vitamin Bmentioning
confidence: 99%
“…Women with an increase in serum folate had infants with greater BL. A study in China found that women with the lowest serum folate levels were more likely to have infants born with fetal growth restriction [ 25 ]. Similar results were found in India, in which pregnant women with greater erythrocyte folate at 28 weeks had infants with greater birth weight [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, HHct was associated with numerous pregnancy complications, including recurrent pregnancy loss (RPL) [34][35][36][37][38][39], preeclampsia (PE) [40,41], preterm delivery [42,43], placental abruption [3,44,45], fetal growth restriction (FGR) [46][47][48], and gestational diabetes mellitus (GDM) [49,50]. However, a number of these findings lack consistency [16,36,[51][52][53][54][55][56][57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%